Characterization of scaffolds based on chitosan and collagen with glycosaminoglycans and sodium alginate addition. (July 2018) - Kaczmarek, B.; Sionkowska, A.; Stojkovska, J.
Abstract: Scaffolds based on chitosan (CTS), collagen (Coll), and glycosaminoglycans (GAGs) cross-linked by sodium alginate (SA) were obtained with the use of the freeze-drying method. They were characterized by different analyses, e.g. infrared spectroscopy, SEM images and differential scanning calorimetry. Furthermore, biomechanical properties of the scaffolds were determined in a biomimetic bioreactor. The results showed that the scaffolds based on chitosan, collagen, and glycosaminoglycans cross-linked by sodium alginate are stable in aqueous environment. The infrared spectroscopy analysis showed the hydrogen bond formation between polymers. Scaffolds presented open-pores structures even after a 3-day long analysis in a perfusion bioreactor. The obtained results indicate that the addition of sodium alginate slightly modified biomechanical properties. Highlights: Scaffolds based on chitosan, collagen, glycosaminoglycans and sodium alginate were obtained by freeze-drying method. Scaffolds were tested in in vivo-like conditions and the improvement of properties was observed for cross-linked samples. Materials presented appropriate parameters such as porosity above 90% and biomechanical stability. The pores size was around 257 μm. Obtained scaffolds properties were appropriate for the biomedical application.